Isolation And Characterization Of Aptamers Against Leptospira Lipl32 - Yeoh, Tzi Shien (2023)
In this study, both DNA and RNA aptamers were developed against LipL32. LepRapt-11 was shown to be the most potent RNA aptamer, with dissociation constant and limit of detection of 350 ± 47.45 and 100 nM as determined by direct Enzyme-linked Aptasorbent Assay (ELASA), respectively.